А был ли раскол в читателях? Об аудитории журналов «Cовременник» и «Русское слово» - Kornackij, Nikolaj (Wiener Slawistischer Almanach, 2024)
This article focuses on the infamous “split among the nihilists” – polemic between two leading Democratic magazines in the 1860s Sovremennik and Russkoe slovo. Based on the concept of “corporate reputation”, the author analyzes how this confrontation influenced the opinions of journalists and the “target audience” about the participants. Undoubtedly, it is the Russkoe slovo that can be considered the main beneficiary. Following the results of the controversy, the magazine of Grigory Blagosvetlov and Dmitry Pisarev managed to win the sympathy of young readers. However, the victory was not complete. Radical segments of the audience (like Dmitry Karakozov’s circle and the Siberian regionals) took the side of Sovremennik.